A RETROSPECTIVE CROSS-SECTIONAL STUDY INVESTIGATING THE PREVALENCE OF COVID-19 AND TB COINFECTION IN PATIENTS IN KWAZULU-NATAL, SOUTH AFRICA. - Hlabisa, Vuyo; Nobuhle Jaya, Ziningi (Student’s Journal of Health Research Africa, 2023)
Background: The co-occurrence of tuberculosis (TB) and Covid-19 pose significant challenges to public health systems worldwide. This study aimed to investigate the prevalence of TB and Covid- 19 co-infection, explore the correlation between TB status and Covid-19 results and examine the distribution of co-infection across different age groups in KwaZulu-Natal, South Africa. Methods: A retrospective analysis was conducted using data retrieved from a laboratory database, including 1241 TB patient results between April 2020 and April 2021. Diagnostic methods for TB included microscopy, culture, GeneXpert, and line probe. Covid-19 test results were categorized as positive, negative, or inconclusive. Statistical analysis, including statistical significance tests, was performed to assess the correlation between TB status, Covid-19 co- infection, and age groups. Results: Among the TB patients, 3.95% were diagnosed using microscopy, 7.01% using culture, 88.80% using GeneXpert, and 0.24% using line probe. Out of the 1241 TB patients, 50% were males and 49% were females. Among the tested patients, 84% tested negative for Covid-19, 14.5% tested positive, and 1% had inconclusive findings. The statistical significance analysis indicated no significant correlation between TB status and Covid-19 co- infection (p > 0.05). However, a significant association was observed between age groups and Covid-19 co-infection (p < 0.05). Conclusion: Although no significant correlation was found between TB status and Covid-19 co-infection, there was a significant association between age groups and co-infection rates. These findings highlight the need for tailored screening, prevention, and treatment strategies considering different age groups. The study contributes to the existing literature and can inform healthcare policies and interventions related to TB and Covid-19 co-infection. Recommendation: To address the co-infection, we recommend strengthening surveillance, enhancing awareness, conducting further research, improving infection control, and developing integrated healthcare approaches.